Utilization of digital platforms in interfaith and intercultural dialogue for inclusive and harmonious religious moderation - Hasnawati (12 Waiheru, 2025)
This study aims to analyze religious moderation and dialogical literacy, as well as the use of digital platforms to promote religious moderation as a strategic step toward achieving Indonesia Emas 2045—an inclusive and harmonious national vision. The primary focus of this study is to investigate the extent to which understanding the values of religious moderation, the effectiveness of digital literacy, and the utilization of information technology can enhance tolerance and interreligious harmony. The research employed a descriptive quantitative method, collecting data through online questionnaires distributed to participants of the Religious Moderation Facilitator Training within the Ministry of Religious Affairs in the Maluku region in 2024. The findings indicate that most respondents demonstrated a high level of understanding of the values of religious moderation. A total of 76.7% strongly agreed that religious moderation fosters social harmony, while 72.1% understood moderation as a rejection of extremism. In the context of digitalization, 48.6% of respondents had used information technology for interfaith dialogue, 38.9% did so regularly, and 55.1% utilized digital platforms to promote moderation. Moreover, 40.6% of respondents rated digital literacy as highly effective, and 30.4% considered it effective in supporting interfaith dialogue. The study contributes by emphasizing that integrating dialogical literacy and digital technology is a crucial strategy for strengthening religious moderation in the global era. These findings provide an empirical basis for education and social policies rooted in digital literacy to foster tolerance, inclusivity, and interreligious harmony in Indonesia.